Microservices : building scalable software : easily build and implement scalable microservices from scratch : a course in three modules /: building scalable software : easily build and implement scalable microservices from scratch : a course in three modules. ([2017?]) - Sharma, Sourabh; RV, Rajesh; Gonzalez, David
No abstract available